PENGARUH VARIASI KONSENTRASI DAN LAMA PERENDAMAN ASAM LAKTAT TERHADAP KADAR GLUKOSA DAN UJI ORGANOLEPTIK TEPUNG UBI JALAR (Ipomoea batatas) - Hidayati, Nasrul Rofiah (Jurnal Florea, 2014)
Science Skills include observing skills with all the senses, using tools and materials, plannedÂ the exThis study aims to investigate the influence of variations in the concentration and dipping time of lactic acid to glucose and organoleptic sweet potato (Ipomoea batatas). The research method using completely randomized design (CRD) with factorial 3x3 and three replications. The first factor is the variation of concentration (K) include 1%, 1.5%, 2%, both long immersion factor (L) includes 60 minutes, 90 minutes, 120 minutes. Collecting data by calculating the glucose level using titration method using Na2S2O and organoleptic tests include color, smell, texture andlevel of preference to the 15 panelists using the enclosed questionnaire. Analysis of data using 3analysis of variance (ANOVA) two paths through SPSS version 17.0 with a significance level of 0.05, then when will significantly dilanjutkanuji LSD or LSD. The analysis showed variationin the concentration effect on glucose levels (P = 0.000 <0.05). Soaking time effect on glucoselevels (P = 0.000 <0.05). There are significant variations in the concentration of interaction and immersion duration of the glucose levels (P = 0.013 <0.05). The highest glucose levels found in K1Ltreatment (1% concentration and dipping time of 60 minutes), while the lowest glucoselevels in the treatment K1 3L2 and K3L on immersion 120 menit.Hasil organoleptic preferred on K3L 3 treatment because the typical smell of sweet potato is missing, whiter color , the texture is very soft and low glucose levels.Keywords: lactic acid, sweet potato (Ipomoea batatas), glucose, organoleptic test